2015
DOI: 10.1186/s13619-015-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell aging in adult progeria

Abstract: Aging is considered an irreversible biological process and also a major risk factor for a spectrum of geriatric diseases. Advanced age-related decline in physiological functions, such as neurodegeneration, development of cardiovascular disease, endocrine and metabolic dysfunction, and neoplastic transformation, has become the focus in aging research. Natural aging is not regarded as a programmed process. However, accelerated aging due to inherited genetic defects in patients of progeria is programmed and resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…However, why the defect of the causative gene WRN causes impaired regenerative capacity and overall senescence is intriguing. One explanation for this phenomenon is the accelerated depletion of the adult stem cell pool (Cheung, Pei, & Chan, ; Zhang et al, ). The availability of a human iPSC/ESC model provides a new approach to test such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…However, why the defect of the causative gene WRN causes impaired regenerative capacity and overall senescence is intriguing. One explanation for this phenomenon is the accelerated depletion of the adult stem cell pool (Cheung, Pei, & Chan, ; Zhang et al, ). The availability of a human iPSC/ESC model provides a new approach to test such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy aging depends on the proper and persistent function of tissue-specific stem cell populations throughout the body (Ahmed et al, 2017; Oh et al, 2014). Numerous studies have shown that a variety of genetic and environmental factors can contribute to dysfunction in stem cell maintenance and self-renewal resulting in premature tissue aging (Cheung et al, 2015; Harris et al, 2018; Inomata et al, 2009; Uno and Nishida, 2016). The dormant state of cellular quiescence (G 0 ) is the primary method by which premature proliferative exhaustion of stem cell populations is prevented with age (Tümpel and Rudolph, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…WRN-deficient hESCs and MSCs show phenotypes of accelerated aging including premature dysfunction such as decreased proliferative potential in addition to increased expression of p16 INK4 and p21 Waf1 , both markers of aging (Cheung et al, 2015;Shimamoto et al, 2014;Wu et al, 2018). Interestingly, WRN-depleted neuronal progenitor cells do not show signs of premature aging, neither do reprogrammed iPSCs, likely due to an increased telomerase activity as a consequence of reprogramming (will be discussed in more detail below) (Cheung et al, 2014;Shimamoto et al, 2014).…”
Section: Wrn Mutation In Stem Cell Exhaustionmentioning
confidence: 99%